Fiscal Adjustments : Determinants and Macroeconomic Consequences - Plekhanov, Alexander (IMF Working Papers; Working Paper ;, 2007)
The paper analyzes the determinants of success of recent fiscal consolidations in the OECD countries as well as the short-run and long-run effects of fiscal adjustments on economic activity by looking at fourteen case studies, panel data for OECD countries, and the results of simulations using a non-Ricardian multi-country dynamic general equilibrium model. The study finds that while fiscal consolidations tend to have short-run contractionary effects, they can be expansionary in the long run, provided that they do not rely excessively on cuts in productive government expenditure. They can also create positive spillover effects for the rest of the world.